DYNAMICS OF INDICATORS CARIES IN CHILDREN WITH VARYING FREQUENCY OF ACUTE RESPIRATORY VIRAL INFECTION DURING PREVENTIVE MEASURES - L. Kaskova; O. Pavlenkova (Український стоматологічний альманах, 2018)
Article is devoted to dynamics of indicators of dental caries in children with varying frequency of acute respiratory viral infections in the process of prevention.